Transformational leadership and work engagement in Muslim workers: The moderating role of gender - Wan Mariah; Suryani Hardjo; Sjahril Effendy (INSPIRA: Indonesian Journal of Psychological Research, 2023)
This study examines the role of transformational leadership on employee work engagement, seen with gender as a moderator variable. This study engaged 190 Muslim employees as a total sample and used quantitative methods with an explanatory approach with two adaptation scales, the Transformational Leadership Scale by Bas & Avolio (1995) and the Work Engagement Scale by Schaufeli, Bakker, and Salanova (2006). The data analysis technique used Structural Equation Modeling (SEM). The results showed the role of transformational leadership in employee work engagement. However, there is no role of gender as a moderator in the influence of transformational leadership on work engagement. The findings of this study contribute to the literature on transformational leadership by explaining how leadership that motivates and inspires can help employees be more engaged in their work.